Mastectomy Patients’ Knowledge Level about Breast Lymphedema Prevention - Kamil, Abbas Hamid; Mrahib , Ayat Ibrahim; Ali, Ammar Abdulkhaleq (Indonesian Journal on Health Science and Medicine, 2025)
Background: Breast cancer-related lymphedema (BCRL) is a prevalent and debilitating complication following breast cancer treatment, significantly impairing patients’ quality of life. Specific Background: Despite its impact, prevention strategies are often underemphasized in post-mastectomy care. Knowledge Gap: Limited patient education and awareness about BCRL preventive measures hinder early intervention. Aim: This study aimed to assess the knowledge level of mastectomized patients regarding BCRL prevention. Methods: A descriptive study was conducted using non-probability sampling at Baqubah Teaching Hospital's Oncology Ward. Data were collected through a structured instrument comprising socio-demographic, clinical, and knowledge-related items and analyzed using descriptive and inferential statistics. Results: Findings revealed a mean knowledge score of 2.26, indicating that the majority of participants had a moderate understanding of BCRL preventive measures. Novelty: This study highlights a critical need for proactive educational interventions targeted at mastectomized patients, emphasizing prevention rather than post-onset management. Implications: Integrating continuous patient education into nursing practice is essential to enhance knowledge and reduce the incidence of BCRL, ultimately improving long-term patient outcomes. Highlights: Early education on lymphedema prevention is crucial post-mastectomy. Most patients demonstrated only moderate knowledge levels. Nurses play a key role in ongoing patient education. Keywords: Breast Cancer, Lymphedema, Prevention, Patient Education, Mastectomy